PENGARUH SELF HELP GROUP TERHADAP KUALITAS HIDUP PASIEN HEMODIALISA DI RUMAH SAKIT PUSAT KESEHATAN UMUM MUHAMMADIYAH YOGYAKARTA - Relawati, Ambar; Hakimi, Mohammad; Huriah, Titih (Jurnal Ilmiah Kesehatan Keperawatan, 2015)
Chronicrenalfailure patientsare requiredtoperformhemodialysis (HD)to replace ofkidney functionhas beendamaged. Hemodialysishas side effectsthatwillaffect the qualityof life of patients. Independentnursingactionsto support improvedquality of life forhemodialysispatientscouldbegroups therapy, one of which is aSelf HelpGroup (SHG). This studyaimed to examinethe influence ofself-help group actionagainst thequality of life ofhemodialysispatientsinPKU MuhammadiyahYogyakartaÂ  hospital. Thisresearchdesignusingquasy experiment withpretest-posttest control group design.The sample selection in this study using total sampling technique. Respondentscontrol groupof 16 peopleandthe intervention groupare 15 people. The respondents in the control group received the standard treatment of the hospital, and the intervention group receive self-help group meeting 8 times Analysis ofthe data usedindependentt-test. Results from the analysis data obtained significant value mean difference test between control group and intervention group before being implemented SHG p value is 0.404, it is means that there is no significant difference quality of life HD patients before implementation SHG.The significant value of the mean difference testbetweenintervention group and control group is p value <0.001, it is means that there are significantly differences quality of life between intervention group and control group. Combination ofHDandselfhelp groupinrenal failurepatients with undergoingHDcan improve thequality of life ofpatients. Selfhelp groupcouldbe appliedtopatients suffering fromchronicdiseasessuch as kidney failureas asupportive therapy.Â Keywords: Quality of Life, hemodialisys, self help group